Erythrostemon sousanus (Leguminosae: Caesalpinioideae), a new species from the Río Papagayo Basin in Guerrero, México - Contreras-Jiménez, José Luis; Sotuyo, Solange; Calvillo-Canadell, Laura; Lewis, Gwilym P. (Phytotaxa, 2017)
A new legume species, Erythrostemon sousanus, from seasonally dry forest of the Río Papagayo Basin in Guerrero, Mexico is described and illustrated. The new species is morphologically similar to E. mexicanus, from which it is distinguished by its glabrous leaves with a greater number of pairs of pinnae (6–11 vs 5–7) and each pinna with more pairs of leaflets (5–7 vs 2–4); by flowers, inflorescences and fruits densely pubescent; and by larger flowers (13–17 vs 12 mm long), fruits (8 × 2 vs 4 × 1.5 cm) and seeds (12 × 9 × 2 vs 9–10 × 7.5 ×1.5 mm).